Optimization of Speed Innovation on the Influence of Customer Orientation on Market Performance - Novie, Muhafidhah; Usada, Untung; Asitah, Nur (SENTRALISASI, 2021)
The number of Small and Medium Enterprises (SMEs) is a business group that is an important part of national economic development. The number of SMEs continues to grow but is not matched by the increase in the marketing performance of these SMEs. This research was conducted to optimize speed innovation as a mediation between customer orientation and market performance. We used 172 samples based on 302 existing populations using stratified random sampling. The research method used in analyzing the relationship between the three variables is Partial Least Squares - Structural Equation Modeling (PLS-SEM). The results of data processing show that speed innovation can mediate customer orientation in improving the market performance. This study contributes to explaining the determinants of market performance for SMEs. The results of this study show that SMEs depend on customer orientation and innovation speed to improve market performance. Customer orientation is proven to improve market performance. Customer orientation has a positive effect on SMEs performance.